Digital Ethics in Leadership Based on Ki Hadjar Dewantara Philosophy - Sri Watini; Budi Supriyatno (ADI Bisnis Digital Interdisiplin Jurnal, 2026)
Speaking ethics is one of the fundamental aspects in shaping a person's character and personality, especially leader of the nation who play an active role as role models in a pluralistic society. In the context of exemplary leadership, particularly in speaking, it provides a strong moral and spiritual foundation for building ethical, courteous, and leadership-oriented communication. This research aims to examine the concept of speaking ethics in providing exemplary leadership based on Ki Hadjar Dewantara's philosophy, emphasizing the application of the values "Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani" in public communication practices. The research method used is a literature study with a descriptive qualitative approach. The findings indicate that the application of speaking ethics based on Ki Hadjar Dewantara's philosophy is capable of strengthening conducive communication in improving the quality of social interaction, as well as cultivating a civilized and character-based communication culture.